Price Discovery for Cross-Listed Securities from Emerging Eastern European Countries - Marco Wölfle (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
This study provides empirical evidence verifying the theory of price discovery for Eastern European enterprises based on their cross-listing on Western European exchanges. Despite the fact that the crosslisting behavior of companies has been analyzed very actively since the mid-70s, many competing hypotheses exist, and the debate is far from reaching an end. Cumulative average residuals (CARs) document increased information efficiency after the listing in Frankfurt or London. This result is supported by a stylized microstructure model. To be precise, competition for order flow alleviates informational frictions and reduces dealers? market power. These properties, however, are unevenly distributed among the auction system Frankfurt and the market maker system London. GARCH volatility spillovers strongly support these results and quantify a dominant role for home markets in information discovery. Moreover, they provide information on the relative functions of Frankfurt and London.
Keywords: D53; C32; G30; G15; G14; F36; 330; Cross-Listing; Cumulative Average Residuals; Eastern Europe; Information Discovery; Time Series; Börsenkurs; Internationaler Finanzmarkt; Wertpapieremission; Informationseffizienz; Unternehmen; Osteuropäisch; Deutschland; Großbritannien